1997
DOI: 10.1093/jnci/89.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 Expression in Bladder Cancer: Association With p53 Alterations, Tumor Angiogenesis, and Tumor Progression

Abstract: These data support the concept that TSP may possess a tumor-inhibitory function. TSP may act, in part, through the regulation of tumor neovascularity. These results may also provide insight into one mechanism by which p53 exerts its tumor suppressor effects, i.e., through the control of tumor angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
168
8
6

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(194 citation statements)
references
References 29 publications
12
168
8
6
Order By: Relevance
“…For example, the expression of cadherins (Takeichi, 1993), SPARC (Jendraschak and Sage, 1996), laminin (Mizushima et al, 1996), thrombospondin (Grossfeld et al, 1997), protein tyrosine phosphatase (CL100) (Loda et al, 1996), and MAGE proteins (Itoh et al, 1996), have been reported to be altered in tumors. It is not known whether any genes identi®ed in this study can be causally linked to the carcinogenesis, but several genes, such as AA112374 (see Figure 6d) that are preferentially expressed in cancer cell lines represent potential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of cadherins (Takeichi, 1993), SPARC (Jendraschak and Sage, 1996), laminin (Mizushima et al, 1996), thrombospondin (Grossfeld et al, 1997), protein tyrosine phosphatase (CL100) (Loda et al, 1996), and MAGE proteins (Itoh et al, 1996), have been reported to be altered in tumors. It is not known whether any genes identi®ed in this study can be causally linked to the carcinogenesis, but several genes, such as AA112374 (see Figure 6d) that are preferentially expressed in cancer cell lines represent potential candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated alterations in THBS1 expression in the neovascularization observed in human cancers (Roberts, 1996): Decreased expression of THBS1 has been reported in multiple primary tumors (Grossfeld et al, 1997;Zabrenetzky et al, 1994;Clezardin et al, 1993) and cells transformed in vitro by c-jun (Mettouchi et al, 1994), Nickel (Salnikow et al, 1994), v-src (Slack and Bornstein, 1994), the polyoma virus middle-t antigen (Sheibani and Frazier, 1995), and v-myc (Tikhonenko et al, 1996). Reexpression of THBS1 reduced tumor growth, angiogenesis and metastasis in a hemangioma cell line (Sheibani and Frazier, 1995) and a breast cancer cell line (WeinstatSaslow et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…32 TSP1 is expressed in normal breast, colon, and bladder epithelium. 10,[33][34][35] In general, TSP1 expression is significantly reduced in cancer cells that arise in these tissues. However, lobular carcinomas in the breast express significantly higher levels of TSP1 and TSP2 than normal tissue.…”
mentioning
confidence: 99%
“…10,[33][34][35] TSP1 expression shows an inverse correlation with vascular density in bladder and colon cancer but does not correlate with vascular density in some other tissues such as ductal breast carcinoma. 10,[33][34][35] Whereas TSP1 may be down-regulated in tumor cells, relatively high levels of TSP1 and TSP2 mRNA and protein are associated with stromal fibroblasts. 33,36 In addition, activated monocytes and macrophages contribute TSP1 to the tumor environment as do endothelial cells.…”
mentioning
confidence: 99%